1990
DOI: 10.1002/ajpa.1330820102
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal biological distance studies in American Physical Anthropology: Recent trends

Abstract: Biological distance analysis, the dominant type of skeletal biological research during the 19th century, has become less visible in recent years. Although the proportion of American Journal of Physical Anthropology articles and published abstracts focusing on biodistance has remained fairly constant over the three decades between 1955 and 1985, the proportion of biodistance contributions relative to other skeletal biology studies has decreased. Emphasis in skeletal biology has shifted from the analysis of biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(65 citation statements)
references
References 23 publications
1
58
0
6
Order By: Relevance
“…Many regional studies examine populations within a single country (e.g., Guatelli-Steinberg et al, 2001), region of a country (e.g., Hubbard, 2012), or bordering countries (e.g., Ullinger et al, 2005). As noted by Buikstra et al (1990), this more refined focus is common in the 5" " bioarchaeological literature and is reflected in an array of more recent publications (e.g., see Blom et al, 1998;Irish, 2006;Coppa et al, 2007;Sołtysiak and Bialon., 2013;Willermet et al, 2013;Irish et al, 2014). Such regional studies often focus on understanding mobility patterns (e.g., McIlvaine et al, 2014), trading networks (Ragsdale and Edgar, 2014), and other social phenomena (e.g., see Knudson and Stojanowski, 2008).…”
Section: Previous Studies Comparing Dental and Genetic Biodistance Esmentioning
confidence: 99%
See 2 more Smart Citations
“…Many regional studies examine populations within a single country (e.g., Guatelli-Steinberg et al, 2001), region of a country (e.g., Hubbard, 2012), or bordering countries (e.g., Ullinger et al, 2005). As noted by Buikstra et al (1990), this more refined focus is common in the 5" " bioarchaeological literature and is reflected in an array of more recent publications (e.g., see Blom et al, 1998;Irish, 2006;Coppa et al, 2007;Sołtysiak and Bialon., 2013;Willermet et al, 2013;Irish et al, 2014). Such regional studies often focus on understanding mobility patterns (e.g., McIlvaine et al, 2014), trading networks (Ragsdale and Edgar, 2014), and other social phenomena (e.g., see Knudson and Stojanowski, 2008).…”
Section: Previous Studies Comparing Dental and Genetic Biodistance Esmentioning
confidence: 99%
“…The pseudo-D 2 statistic was used in the present study and calculated using an executable program by Konigsberg (1990). A benefit of the pseudo-D 2 statistic is that it accounts for trait intercorrelation and weights correlated traits (rather than removing them from the sample).…”
Section: " "mentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that the interest in in- fracranial nonmetric traits has coincided with a decline in biologic distance studies. A survey of skeletal biologic distance studies (Buikstra et al, 1990) showed a shift away from such studies from 1965 to 1980, with a slight increase in 1986. It also noted a shift away from interracial and interpopulation studies to those of intraregional and intrasite distance studies.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, biodistance studies have been employed to reveal intrasite genetic variation (Buikstra et al, 1990;Stojanowski and Schillaci, 2006). This technique has been applied several times to Jomon populations (Kondo, 1994;Matsumura and Nishimoto, 1996) and has also been cross-checked against ancient DNA data (Shinoda et al, 1998;Adachi et al, 2003Adachi et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%